Histomorphological changes in the rat pancreas after methionine administration - Yanko, R.; Levashov, M.; Chaka, O.; Safonov, S. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2020)
The effectiveness of using various methionine preparations for activating pancreatic function is ambiguous; the reasons may include differences in dosage and duration of methionine administration. The question remains, in what extent the methionine application is efficacious for increasing functional activity of a healthy pancreas. The aim of our study was to investigate morphological changes in pancreas after prolonged administration of methionine. The experiments were carried out on 24 males of Wistar rats at the age of 15 months. During 21 days, the experimental animals received methionine at a daily dose of 250 mg/kg of body weight in addition to the standard diet. Histological preparations were made from pancreatic tissue according to standard method. Morphometry was performed using the computer program «Image J». The rats were taken out of the experiment under ether anesthesia. The studies were carried out in accordance with the provisions of the "European Convention for the Protection of Vertebrate Animals used for Experimental and Other Scientific Purposes" (Strasbourg, 1986). Upon completion of the experiment, histomorphological sings of an increase in functional activity were registered in both exocrine (enlarged acini’s areas and their epithelium height, higher nuclear-cytoplasmic ratio of exocrinocytes, and higher number of nucleoli in cell nuclei) and endocrine (enlarged sizes of the Langerhans islets and increased number of endocrinocytes in the islets) parts of the rat pancreas. In the experimental rats, the relative area of ​​the connective tissue and the stromal-parenchyma index of the pancreas, as well as the width of the interlobular and interacinus layers of connective tissue decreased. A decrease in the mass of connective tissue in the pancreas can be considered as one of the signs of its function activation, an improvement in metabolism between acini, and an increase in regenerative capabilities. Thus, additional administration of prophylactic doses of methionine to healthy animals results in distinct morphological signs of increased pancreatic activity.